PENEGAKAN HUKUM TERHADAP TINDAKAN KEKERASAN SEKSUAL DALAM APLIKASI BUMBLE - Deviana Cahya Fitri, (2024)
In Indonesia, many incidents occur as a result of this online dating activity. There is a considerable number of crimes affecting victims who have met through social media, especially dating applications. Initially, everything seems positive, with communication between perpetrators and victims going well, even reaching the stage of engaging in virtual sexual activities, sometimes voluntarily or due to the seduction of the perpetrators. Law enforcement is an effort to prioritize the principles of justice, legal certainty, and social benefit. Essentially, law enforcement is the process of actualizing these ideas, involving efforts to ensure that legal norms function effectively as guidelines for actors in legal interactions and relationships in the collective life of society and the state. According to Law Number 23 of 2004, Article 1 paragraph (4), legal protection refers to all efforts aimed at providing a sense of security to victims, which can be carried out by family members, lawyers, social institutions, the police, the prosecutor's office, the judiciary, or other parties, either temporarily or based on court decisions. In the context of this research, the type of research used is normative legal research. This research approach is conducted through the analysis of literature, including legislation, legal theories, and views from legal experts. This study focuses on evaluating the implementation of positive legal principles that apply. Law enforcement against perpetrators of sexual violence can be charged with Law Number 22 of 2022, Optimizing legal protection for victims of sexual violence involves providing legal rights, obligations and assistance, as well as improving the security system in the Bumble Application. This optimization must be carried out by law enforcement authorities with indiscriminate justice so that other communities do not suffer the same fate as victims in the future.